¿Por qué enseñar español? The experiences of bilingual teachers under the leadership of monolingual principals: an ethnographic case study - Mejía Vélez, María del Pilar (Kansas State University, 2017)
Bilingual education has a long history in the United States, although the support for bilingual education through, which students preserve their culture and heritage language, has not been consistent throughout the years. While there is clear evidence that aligns students’ academic, emotional, and economic successes are aligned when they learn English through their native language, there is a paucity of research regarding bilingual principals as leaders of dual-language programs. This study explores issues of challenges and essential support structures within dual-language programs. The results may be used to improve leadership in bilingual programs. The purpose of this ethnographic case study was to explore the lived experiences of two Latinas who taught in Spanish within dual-language programs that were run by monolingual principals. This qualitative study was informed by two different sampling procedures, purposeful and criterion-based. The participants selected needed to be Latina (self-identified), Spanish dual-language teachers who worked with a monolingual principal as their leader within Midwestern U.S. schools, during the 2012-2013 school year. Narrative inquiry grounded the study in order to elicit stories that would represent the experiences of the teachers as they negotiated their path when their leader was monolingual and they taught in Spanish. Findings indicate that teachers who taught in Spanish within an Anglo-majority educational context, experienced palpable manifestations of inequity and discriminations. The participants had strong self-worth, self-confidence, and self-awareness, which led them to persevere through the instances of judgment and imbalance. The finding also demonstrate that the participants developed coping mechanisms to empower themselves, and established newly-found and increased resourcefulness as an attempt to provide the students with the education they deserved. The participants relied on alternative resources, long hours of research and re-planning, creativity, and resolve to function in an environment that was set out to demean them. The study raised implications about the amount of support teachers in bilingual programs who teach in Spanish receive while led by monolingual principals. Another implication is that there is marginalization of certain languages that are not English. Lastly, this study raised implications regarding ways in which bilingual programs can become more just and egalitarian.
Keywords: Dual language; Bilingual education; LatCritBilingual